Pengaruh Reputasi KAP, Ukuran Perusahaan, Fee Audit Terhadap Audit Delay - Fildza Ghaisani Farahiyah Hernadi; Agus Munandar (UNIVERSITAS KALBIS, 2022)
Audit Delay is the length of time the audit is completed measured from the date of closing of the yearbook until the publication of the audited financial statements. The length of the process is a constraint that can influence decision making and the declining reliability of financial information to be published. This research was conducted at manufacturing companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. Samples taken in this study amounted to 36 companies with a 5-year observation period, then obtained a total of observations, as many as 180 observations. This study uses a purposive sampling technique in data collection techniques. The results of this study are the public accontant reputation has no effect on audit delay, company size has a positive effect on audit delay, and audit fees have a positive effect on audit delay.